2021
DOI: 10.1093/cid/ciab560
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Trends in Urine Escherichia coli Isolates From Adult and Adolescent Females in the United States From 2011 to 2019: Rising ESBL Strains and Impact on Patient Management

Abstract: Background Uncomplicated urinary tract infection (uUTI) is predominantly caused by Escherichia coli, which has increasing antimicrobial resistance (AMR) at the US-community level. As uUTI is often treated empirically, assessing AMR is challenging and there are limited contemporary data characterizing period prevalence in the US. Methods This was a retrospective study of AMR using Becton, Dickinson and Company Insights Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 26 publications
5
65
1
Order By: Relevance
“…Our data are consistent with increases in Enterobacterales isolates with ESBL-producing phenotypes noted in a regional study of outpatients in the southeastern US [ 18 ] and in hospitalized US patients [ 15 , 19 ], as well as in E. coli urinary isolates in Canadian [ 6 ] and US outpatients [ 7 ]. Together, these findings indicate that Enterobacterales isolates with an ESBL-producing phenotype remain an important concern for patients with community-acquired UTIs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our data are consistent with increases in Enterobacterales isolates with ESBL-producing phenotypes noted in a regional study of outpatients in the southeastern US [ 18 ] and in hospitalized US patients [ 15 , 19 ], as well as in E. coli urinary isolates in Canadian [ 6 ] and US outpatients [ 7 ]. Together, these findings indicate that Enterobacterales isolates with an ESBL-producing phenotype remain an important concern for patients with community-acquired UTIs.…”
Section: Discussionsupporting
confidence: 89%
“…Most community-onset uncomplicated UTIs (uUTIs) are caused by members of the Enterobacterales family, including Escherichia coli , Klebsiella pneumoniae , and Proteus mirabilis [ 3 ]. Increasing rates of antimicrobial resistance in ambulatory UTI Enterobacterales isolates have obscured disease management [ 4 7 ]. Antibiotic-resistant UTIs are associated with high rates of discordance between antibiotic selection and isolate susceptibility and with treatment failure [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of ARGs present in stool using metagenomics and qPCR has been well studied (Hu et al 2013a(Hu et al , 2013bRose et al 2017;Feng et al 2018) and in urine mostly studied in the limited context of urinary tract infections (Li et al 2020;Kaye et al 2021). However, the clinical relevance of ARG detection in metagenomic data is poorly understood since the presence of ARGs in faecal samples does not necessarily result in AMR infections, even in high-risk patients (Tacconelli et al 2009;Wryes et al 2021).…”
Section: Presence Of Amr In Human Stool and Urinementioning
confidence: 99%
“…In pregnant women with bacteriuria, 83% of E. coli were multidrug-resistant. Kaye et al ( Kaye et al, 2021 ) performed a retrospective study of 1.5 million Escherichia coli isolates from the United States. They found that 14.36% of E. coli isolates in urine samples in adult and adolescent females showed a non-susceptible phenotype to multiple drugs.…”
Section: Conventional Treatment Of Urinary Tract Infections In Pregna...mentioning
confidence: 99%